Voltammetric Quantification of Anti-Cancer Antibiotic Bleomycin Using an Electrochemically Pretreated and Decorated with Lead Nanoparticles Screen-Printed Sensor - Kozak, Jedrzej; Tyszczuk-Rotko, Katarzyna; Metelka, Radovan (MDPI, 2023)
In this paper, we report a highly sensitive voltammetric sensor for the determination of the anti-cancer antibiotic bleomycin (BLM) based on a screen-printed carbon sensor that is electrochemically pretreated and decorated with lead nanoparticles in the sample solution (pSPCE/PbNPs). These sensor surface manipulations contribute to significant amplification of the analytical signal and improvement of its shape and repeatability. The effect of the electrochemical behavior of BLM on the pSPCE/PbNPs was examined by electrochemical strategies. CV, EIS, and XPS were used to compare the sensor surface modifications. The effects of the type and pH of the supporting electrolyte and the procedure parameters were optimized. The features of the proposed procedure include: (a) very low limits of detection and quantification (2.8 x 10(-11) and 9.3 x 10(-11) M, respectively), (b) linear ranges (1.0 x 10(-10)-2.0 x 10(-9) M and 2.0 x 10(-9)-2.0 x 10(-8) M, and (c) a high sensitivity of 0.32 mu A/nM. The electrochemical sensor was successfully applied for the determination of BLM in wastewater and reference material of human urine samples.
Voltametrické stanovení protinádorového antibiotika bleomycin s využitím elektrochemicky předupraveného tištěného senzoru s nanočásticemi olova
Keywords: electrochemically prepared screen-printed carbon electrode; lead nanoparticles; anti-cancer antibiotic; bleomycin; voltammetry; human urine and wastewater sample; elektrochemicky upravená uhlíková tištěná elektroda; nanočástice olova; protinádorové antibiotikum; bleomycin; voltametrie; vzorky lidské moči a odpadních vod